2018
DOI: 10.1519/jpt.0000000000000113
|View full text |Cite
|
Sign up to set email alerts
|

First-Person Perspective Action Observation Training in Individuals With Parkinson's Disease: A Consideration-of-Concept Controlled Pilot Trial

Abstract: This pilot study suggests that FPP AOT is a feasible intervention and the research protocol designed would be suitable, with minor modifications, for the conduction of a subsequent stage 2 trial designed to verify the hypothesis that the adjunct of FPP AOT might improve motor performance in individuals with IPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…Our finding that the performance of the RM sequence improved following either type of instruction corroborates earlier findings, i.e., that AO may be useful as a tool for improving motor abilities in neurological (Ertelt et al, 2007;Pelosin et al, 2010Pelosin et al, , 2013Sugg et al, 2015;Patel, 2017;Giorgi et al, 2018;Peng et al, 2019) and orthopedic (Bellelli et al, 2010;Park et al, 2014) conditions. This plus the finding that the performance of the RM sequence continued to improve in the retest for subjects who passively observed it are important because it is very easy to implement this type of instruction during AO training, at least for some patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that the performance of the RM sequence improved following either type of instruction corroborates earlier findings, i.e., that AO may be useful as a tool for improving motor abilities in neurological (Ertelt et al, 2007;Pelosin et al, 2010Pelosin et al, , 2013Sugg et al, 2015;Patel, 2017;Giorgi et al, 2018;Peng et al, 2019) and orthopedic (Bellelli et al, 2010;Park et al, 2014) conditions. This plus the finding that the performance of the RM sequence continued to improve in the retest for subjects who passively observed it are important because it is very easy to implement this type of instruction during AO training, at least for some patients.…”
Section: Discussionsupporting
confidence: 91%
“…This has been demonstrated among healthy individuals in various motor tasks such as sports activities (Weeks and Anderson, 2000;Horn et al, 2007), novel tasks (Mattar and Gribble, 2005), and force tasks (Porro et al, 2007). Positive behavioral effects of action observation (AO) training have been shown also in neurological conditions such as stroke (Ertelt et al, 2007;Sugg et al, 2015;Patel, 2017;Peng et al, 2019), Parkinson's disease (Pelosin et al, 2010(Pelosin et al, , 2013Giorgi et al, 2018), cerebral palsy (Buccino et al, 2012;Sgandurra et al, 2013), and orthopedic conditions (Bellelli et al, 2010;Park et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a third-person perspective was adopted to improve upper limb bradykinesia (18). To date, a single pilot study, which was not included in our review due to the lack of random allocation, explored the feasibility of AOT delivered from a first-person perspective to improve balance and mobility in patients with PD, revealing potential benefits (52).…”
Section: Characteristics Of the Stimulimentioning
confidence: 99%
“…A largescale study of home-based dexterity training in PD [10] found improvements on both subjective and objective measures. However, to our knowledge, only one previous study has investigated effects of AO training -without MI -on dexterity in people with PD, where improved performance on a peg test was found [43].…”
Section: Outcomes Of Ao+mi Training In Pdmentioning
confidence: 96%
“…Small-scale intervention studies in PD have provided preliminary evidence that AO combined with physical practice can improve motor symptoms, balance and gait [41,42], as well as dexterity [43] and functional independence [44]. Increased activation in cortical motor areas has also been found following AO-based training in PD [41], suggesting potential neuroplastic effects.…”
Section: Action Observation and Motor Imagery As Tools To Facilitate mentioning
confidence: 99%